A qualitative case study of critical literacy in boosting EFL students’ critical language awareness: Critical literacy in teaching exposition text and its impacts - Raden Aulia Utami Hidayat; Sri Setyarini; Gin Gin Gustine; Budi Hermawan (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Critical literacy is essential to be implemented in this 21st-century education. However, the implementation of it remains underexplored, especially in the Indonesian context. This study aims to investigate the implementation of critical literacy in teaching exposition texts and its impacts on students' critical language awareness. Using a qualitative approach with a case study design, the research involved an English teacher and thirty-six tenth-grade students of a public senior high school in one district in West Java, Indonesia. Data were collected through classroom observations. The data were analyzed using deductive thematic analysis based on the four-dimension framework of critical literacy and the five-step guided instructional approach as the guideline. Findings indicated that the teacher has successfully implemented the critical literacy strategies in teaching exposition texts. Furthermore, the practices enhanced students’ critical language awareness by encouraging analytical text evaluation. However, there were two main challenges, particularly in engaging with socio-political issues and taking action since both the teacher and students were still unfamiliar with the discussion of sensitive issues. The study highlights the practical and pedagogical benefits of critical literacy in underrepresented educational settings, contributing to the preparation of a globally competitive and socially aware generation.